Synthesis and Physical Properties of Alkaline Earth Metal Doped La9.67Si6O26.5 Oxyapatite Solid Electrolyte - Yadav, Ashish Kumar (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Synthesis Alkaline Earth Metal; Physical Properties of Alkaline Earth Metal; Doped La9.67Si6O26.5; Oxyapatite Solid Electrolyte